Advanced techniques for audio watermarking - Thanki, Rohit M. (Switzerland : Springer, 2020)
This book provides information on digital audio watermarking, its applications, and its evaluation for copyright protection of audio signals - both basic and advanced. The author covers various advanced digital audio watermarking algorithms that can be used for copyright protection of audio signals. These algorithms are implemented using hybridization of advanced signal processing transforms such as fast discrete curvelet transform (FDCuT), redundant discrete wavelet transform (RDWT), and another signal processing transform such as discrete cosine transform (DCT). In these algorithms, Arnold scrambling is used to enhance the security of the watermark logo. This book is divided in to three portions: basic audio watermarking and its classification, audio watermarking algorithms, and audio watermarking algorithms using advance signal transforms. The book also covers optimization based audio watermarking.
También disponible en formato EPUB